Highly Sensitive Detection of Gallic Acid in Food Samples by Using Robust NiAl2O4 Nanocomposite Materials. Issue 2 (1st January 2019) - Sivakumar, Mani; Pandi, Karuppiah; Chen, Shen-Ming; Yadav, Sudesh; Chen, Tse-Wei; Veeramani, Vediyappan
Abstract : We have successfully synthesized nanostructured cubic NiAl2 O4 nanoparticles for the selective electrochemical determination of gallic acid (GA) and the prepared nanostructured composite material was characterized by (X-ray diffraction, Fourier transform infrared spectroscopy, and field-emission scanning electron microscopy analyses. The cubic NiAl2 O4 nanoparticles had average sizes of ∼ 26–30 nm as calculated from XRD and SEM measurements, respectively. GA-detection performance was also evaluated by cyclic voltammetry and amperometry method. NiAl2 O4 glassy carbon electrode showed excellent performance in GA detection with a linear range, detection limit (SNR = 3 sb/S), limit of quantitation (LOQ = 10 sd/S) and sensitivity value of 0.03–551.18 μM, 0.018 μM, 0.057 μM and 9.019 μM mA −1 cm −2, respectively. The GA sensor was also used in real-sample analysis using food samples, and results showed the practicability of the proposed sensor.